Optimizing the spatial distribution of dose in X-ray macromolecular crystallography. - Zeldin, O; Gerstel, M; Garman, E (2013)
X-ray data collection for macromolecular crystallography can lead to highly inhomogeneous distributions of dose within the crystal volume for cases when the crystal is larger than the beam or when the beam is non-uniform (gaussian-like), particularly when crystal rotation is fully taken into account. Here the spatial distribution of dose is quantitatively modelled in order to compare the effectiveness of two dose-spreading data-collection protocols: helical scanning and translational collection. Their effectiveness in reducing the peak dose per unit diffraction is investigated via simulations for four common crystal shapes (cube, plate, long and short needles) and beams with a wide range of full width half maximum values. By inspection of the chosen metric, it is concluded that the optimum strategy is always to use as flat (top-hat) a beam as possible and to either match the beam size in both dimensions to the crystal, or to perform a helical scan with a beam which is narrow along the rotation axis and matched to the crystal size along the perpendicular axis. For crystal shapes where this is not possible, the reduction in peak dose per unit diffraction achieved through dose spreading is quantified and tabulated as a reference for experimenters.